Mesoporous NH4NiPO4·H2O for High-Performance Flexible All-Solid-State Asymmetric Supercapacitors - Liu, Yong; Zhai, Xiaoliang; Yang, Keke; Wang, Fei; Wei, Huijie; Zhang, Wanhong; Ren, Fengzhang; Pang, Huan (Frontiers in Chemistry, 2019)
Nowadays, wearable energy storage devices have been growing rapidly, but flexbile systems with both exellent cycling stability and decent flexibility are still challenging. In this work, a flexible all-solid-state NH4NiPO4•H2O//graphene supercapacitor with remarkable performance was successfully assembled. When cycled at a current density of 5 mA cm-2, the device delivered 121 mF cm-2, and showed good cycling stability after 3000 cycles. Moreover, the all-solid-state NH4NiPO4•H2O//graphene supercapacitor also exhibit high mechanical flexibilty with well-maintained specific capacitance, even under bending to arbitrary angles (up to 180°) and different weights (up to 50 g).